Social Customer Relationship Management and Organizational Characteristics - Kantorová, Kateřina; Bachmann, Pavel (My University, 2018)
Social customer relationship management (SCRM) is a new philosophy influencing the relationship between customer and organization where the customer gets the opportunity to control the relationship through social media. This paper aims to identify (a) the current level of SCRM and (b) the influence of basic organizational characteristics on the SCRM level. The data were gathered through a questionnaire distributed to 362 organizations headquartered in the Czech Republic. The questionnaire comprised 54 questions focusing on the significance of marketing and CRM practices, establishing a relationship with the customer, online communities, the use of social media in marketing, and acquiring and managing information. Scalable questions with a typical five-level Likert scale were applied in the questionnaire. The results show that larger firms more often set up their own online communities and manage them strategically; moreover, they are able to manage information better. Contrariwise, small-sized organizations use social networks as a way to establish communication with the customer more than large-sized entities. The use of social media for marketing purposes is significantly higher in organizations oriented to consumer markets than in those oriented to business markets.
Vztahy se zákazníky na sociálních sítích a organizační charakteristiky
Keywords: customer relationship management (CRM); social media; social CRM; customer information; small and medium enterprises (SMEs); řízení vztahů se zákazníky (CRM); sociální média; sociální CRM; informace pro zákazníky; malé a střední podniky (MSP)